Becoming part of the city: Influences on the career choice of an urban music educator. (August 2018) - Eros, John
The purpose of this case study was to examine and describe the life experiences that influenced one music teacher's career choice to teach music in an urban school. The primary research question is: What experiences influenced the participant to pursue urban music education as a career? Calling upon research into urban music education and career choice, the article used a "secondary analysis" of survey, journal, and interview data collected in a larger investigation of the teacher career cycle, as viewed through the lens of narrative research. Findings are presented in four categories, and indicate that the teacher's career choice was influenced by three primary elements: (a) feeling a need to be of service to others; (b) experiencing cultural differences; and (c) curiosity about the city; all of which led to (d) being a part of the city. These elements combined to form not just a career choice, but a strong sense of commitment to teaching music in a specific city. Implications for both urban music education and music teacher education are discussed, as are suggestions for further research.